FEEDING PRACTICES AS A DETERMINANT OF EARLY CHILDHOOD CARIES: A CLINICAL AND LABORATORY STUDY (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Background. Early childhood caries (ECC) remains one of the most prevalent chronic diseases in children worldwide. Feeding practices during infancy play a crucial role in shaping oral homeostasis and caries susceptibility. Objective. To evaluate the impact of different feeding practices on dental status and caries development in children of early age. Materials and Methods. A total of 173 children aged 6 months to 6 years with ECC were examined. Participants were stratified by age and feeding practice (breastfeeding, mixed feeding, artificial feeding). Dental status was assessed using caries intensity (dmft index), caries prevalence, caries increment, and oral hygiene indices. Statistical analysis was performed using SPSS software with significance set at p
Keywords: Early childhood caries, feeding practices, breastfeeding, artificial feeding, dental status, prevention.